Design and optimization of the shape of the roller generatrix of double-row railway roller bearing - Хавин, Валерий Львович; Ягудин, Дмитрий Сергеевич (Eastern-European Journal of Enterprise Technologies, 2014)
The paper considers constructing a parametric model of the double-row railway roller bearing and determining the optimal shape of its roller to reduce contact pressure. Solution of problems of one-and two-parameter roller shape optimization, ensuring maximum uniform contact pressure distribution, is achieved by forming the roller geometry by varying the radius of curvature of the roller generatrix, or by varying the two radii that describe the change in the generatrix curvature. The level of maximum contact pressure was considered as the objective function. To determine the contact pressures, finite element method in the formulation of the contact problem of elasticity theory was used. Numerical solution of the contact problem was performed by expanding Lagrange’s method; ANSYS software package was used. Solution of problems of one-and two-parameter roller surface shape optimization was carried out by applying the penalty function method in combination with the alternating-variable descent method and the golden section search method. Optimal radii of curvature of roller generatrix of double-row railway roller bearing CRU 150x250 in the formulation of one-and two-parameter optimization problem were obtained. It was revealed that the roller generatrix geometry in the form of two conjugated radii of curvature ensures maximum contact pressure level by 8% lower than in forming the roller surface curvature by a single radius of curvature. The results show the possibility of a significant reduction of the contact pressure for a pair of roller - bearing race due to the optimal profiling of roller generatrix, which will allow proportionally increase the durability and life of the product.